Innovative approaches in the organization student learning - Sh.B. Akhmedova (International Consortium of Education and Culture Research Studies, 2019)
This paper makes analyses of the innovative approaches in the organization student learning. On this case, research gets points of both theoretical and methodological aspects to get better results. It concludes with the vivid results to make further analyses in the future investigations.